Modelling Between Digital and Humanities Thinking in Practice - Ciula, Arianna (Open Book Publishers, 2023)
This volume presents an exploration of Digital Humanities (DH), a field focused on the reciprocal transformation of digital technologies and humanities scholarship. Central to DH research is the practice of modelling, which involves translating intricate knowledge systems into computational models. This book addresses a fundamental query: How can an effective language be developed to conceptualize and guide modelling in DH? Modelling, with its historical roots, carries multifaceted meanings influenced by various disciplinary contexts. Modelling Between Digital and Humanities innovatively connects DH with the historical tradition of model-based thinking in the humanities, cultural studies, and the sciences. It endeavors to reshape interpretative frameworks by contextualizing DH's modelling practices within a broader conceptual landscape. Through an exploration of digital, visual and data models, the book asserts that DH holds the potential to be a cornerstone of a novel cultural literacy paradigm. By probing the interplay between technology and thought, the book ultimately positions DH as a catalyst for transformative cultural insights.